The Importance of Collaborative Teaching Technology in Social and Humanitarian Sciences - Rakhmatova Mexrinoz Majitovna (International Journal on Integrated Education, 2023)
This article presents the technology of cooperative teaching in social and humanitarian sciences, the methodology of working in small groups. The positive results provided by this technology in the course of the lesson have been revealed.